Study of Repairs and Various Post-Seismic Interventions Carried Out in Ancient Sites in Algeria - Benmehidi Said; Bordjiba Abdelhak (Selected Scientific Papers: Journal of Civil Engineering)
Centuries of accumulated experience in construction during ancient times led to considerable expertise. Roman builders, for example, honed their engineering and construction skills to a high degree, even factoring in considerations for seismic hazards. Through an examination of the vestiges of Roman civilization, one can discern various parallels between the structures found in Europe and those in Roman Africa, particularly in the methods employed for repairs labeled by scholars as post-seismic restoration. The investigation took place across multiple historic locations in Algeria, including Djemila, Timgad, and Lambèse, aiming to examine the possible correlation between previous renovations and seismic activity. This was achieved through visual examination and comparative analysis with findings from Italian sites such as Pompeii and Ostia.